Recurrence of tropical cyclones and their impact on the rains in Iraq: a case study (Baghdad Station) - Al-Shammari, Hussein Jabr (Al-Adab Journal, 2020)
The research aims to prove the relationship between the high number of tropical cyclones in the eastern region of the North Atlantic Ocean and the amounts of rain recorded in Iraq, as the research assumes that the cyclones that follow in their path a movement similar to the letter (C) affect the amount of rain recorded on the Baghdad station, the study reached proof The existence of a relationship between the increase in the average duration of tropical cyclones in the eastern tropical region of the Atlantic and the decrease in monthly rainfall amounts at the Baghdad station. The high frequency of days of stay in the eastern region of the Atlantic depends on the activity of tropical cyclones and that any increase in tropical cyclone activity will enter Higher latitude circles than usual to be active in, so it will enter the western region, and consequently, there will be greater energy consumption, i.e. water vapor, and as a result, the quantities of water vapor that the atmospheric depressions can bring will decrease.